Raymond : design of warehouse operations - Roy, Debjit, (SAGE Knowledge. Cases., 2015)
On 16 July 2014 at 9 a.m., the meeting commenced at the Chhindwara (Nagpur, India) textile plant of Raymond Limited. Avnish Naik, Deputy General Manager (Warehouse), was in a discussion with warehouse management system consultants. They were contemplating how to improve warehouse operations and increase the storage capacity at the plant. In the recent past, Raymond had witnessed a series of order cancellations because of long delays in order fulfillment (the underpicking rates were more than 20%). The productivity of picking and inbound processes was declining, and the manpower requirement was at an all-time high with overtime of approximately 5,000 man days per year. Due to lack of substantial organisation of SKUs (stock keeping units) within bins, it took up to 12 days to complete the annual stock audit procedure. The company was at a risk of losing valuable clients if the warehouse management issues were not immediately rectified.